Physics implication from higher weak isospin decomposition - Phung Van Dong; Duong Van Loi (European Physical Journal C: Particles and Fields, 2023)
Abstract The $$SU(3)_L\otimes U(1)_X$$ S U ( 3 ) L ⊗ U ( 1 ) X symmetry actually studied is directly broken to the electroweak symmetry $$SU(2)_L\otimes U(1)_Y$$ S U ( 2 ) L ⊗ U ( 1 ) Y by a Higgs triplet, predicting a relevant new physics at TeV scale. This work argues, by contrast, that the higher weak isospin $$SU(3)_L$$ S U ( 3 ) L might be broken at a high energy scale, much beyond 1 TeV, by a Higgs octet to an intermediate symmetry $$SU(2)_L\otimes U(1)_{T_8}$$ S U ( 2 ) L ⊗ U ( 1 ) T 8 at TeV, before the latter $$U(1)_{T_8}$$ U ( 1 ) T 8 recombined with $$U(1)_X$$ U ( 1 ) X defines (i.e., broken to) $$U(1)_Y$$ U ( 1 ) Y by a Higgs singlet. The new physics coupled to $$SU(3)_L$$ S U ( 3 ) L breaking phase is decoupled, whereas what remains is a novel family-nonuniversal abelian model, $$U(1)_{T_8}\otimes U(1)_X$$ U ( 1 ) T 8 ⊗ U ( 1 ) X , significantly overhauling the standard model as well as yielding consistent results for neutrino mass, dark matter, W-mass anomaly, and FCNC, differently from the usual 3-3-1 model.